Analysis of students’ scientific argumentation using the SOLO taxonomy on hydrocarbon material through a socio-scientific issues (SSI) approach - Tritiyatma Hadinugrahaningsih; Yuli Rahmawati; Rika Siti Syaadah; Adam Julio Waskito; Fatikhah Widya Rahmadani; Dzakiyyah Alfina Hanum; Devita Marlina Vanessa (EDUSAINS, 2026)
This study aims to identify the argumentation profiles of students on the topic of carbon compounds using a socio-scientific issues (SSI) approach. The research was conducted at one of public senior high schools in Tangerang involving 32 twelfth-grade students. A mixed methods were employed. The research instruments included observation sheets, reflective journals, argumentation tests, student worksheets, and interviews. The results indicate that chemistry learning on carbon compounds through the socio-scientific issues (SSI) approach created a more engaging learning environment, as the discussions and problem topics were closely related to everyday life. The students’ argumentation profiles generally demonstrated multi-structural abilities in the components of evidence and reasoning, with respective percentages of 81% and 50%. Meanwhile, the components of rebuttal and claim were still at pre-structural and unistructural levels, with a unistructural percentage of 50% and 72%, respectively. These findings suggest that although the Socio-scientific Issues (SSI) approach has been effective in developing students' abilities to provide evidence and reasoning, their skills in constructing strong claims and presenting appropriate rebuttals still require further improvement.